Holy Protection：Jewish Policies of Pope Gregory the Great - MA, Nan (Journal of Research for Christianity in China (JRCC), 2025)
During the papacy of Gregory the Great, he adopted a tolerant and friendly attitude and asylum policies toward the Jews as a whole. The attitude and policies are based on his theological thought, the local Roman laws, the chaotic social environment of Rome and the important role in trade that Jews played. The tolerant attitude and the lenient policies had extremely profound influence to the later generation.